Parallel Algorithms and Software for Nuclear, Energy, and Environmental Applications Part I: Multiphysics Algorithms (Communications in Computational Physics, 2012)
There is a growing trend within energy and environmental simulation toconsider tightly coupled solutions to multiphysics problems. This can be seen in nuclear reactor analysis where analysts are interested in coupled flow, heat transfer andneutronics, and in nuclear fuel performance simulation where analysts are interestedin thermomechanics with contact coupled to species transport and chemistry. In energy and environmental applications, energy extraction involves geomechanics, flowthrough porous media and fractured formations, adding heat transport for enhancedoil recovery and geothermal applications, and adding reactive transport in the case ofapplications modeling the underground flow of contaminants. These more ambitioussimulations usually motivate some level of parallel computing. Many of the physicscoupling efforts to date utilize simple code coupling or first-order operator splitting,often referred to as loose coupling. While these approaches can produce answers, theyusually leave questions of accuracy and stability unanswered. Additionally, the different physics often reside on distinct meshes and data are coupled via simple interpolation, again leaving open questions of stability and accuracy.